Potensi Pembangkit Listrik Tenaga Bayu Secara Ekonomi di Kawasan Wisata Pantai Cermin Menggunakan Software Homer - Yulianti Purba, Darma; Zambak, Muhammad Fitra; Rohana; Helena T Hutabarat, Purnama (Universitas Medan Area, 2024)
The Wind Power Plant is an alternative energy source for generating electricity. The development and utilization of wind energy technology is an effort to increase the contribution of renewable energy to the supply of electrical energy, especially in areas that are not covered by the PLN electricity network. Economic analysis is the application of financial analysis to determine the feasibility of a wind power generation system in the Cermin Beach tourist area, Deli Serdang Regency. Simulation results using Homer software were obtained to supply a load with a kWh of 1,144 kWh/day, a wind turbine with a capacity of 10 kW required 3 turbines with an output power of 2001 watts per turbine. The cost of constructing the turbine after the simulation is Rp. 5,400,000,000 where the total production value if using this generator is IDR 45,709 /kWh, whereas if using the PLN tariff it is IDR. 45,789/kWh with a pay back period of 140 years. The wind speed is 2.63m/s. The mass flow rate is 133.46kg/s, the efficiency power is 1600 watts and the system power is 18.9 watts/m2.